THE EFFECT OF JIGSAW TECHNIQUE TO TEACH READING NARRATIVE TEXT TO THE TENTH GRADE STUDENTS OF SMAN 1 PATIANROWO (RETAIN, 2016)
THE EFFECT OF JIGSAW TECHNIQUE TO TEACH READING NARRATIVE TEXT TO THE TENTH GRADE STUDENTS OF SMAN 1 PATIANROWO Shendy Mega Rahmawati English Education Department, Language and Arts Faculty, Surabaya State University Email: shendyrahmawati@mhs.unesa.ac.id Fauris Zuhri S.Pd., M.Hum. English Education Department, Language and Arts Faculty, Surabaya State University Email: Fauriszuhri@gmail.com Abstract Reading is a receptive skill that should be learnt by the students before they learn the other skill. Based on the researcher’s pre-observation the students often feel that reading is a boring activity in the classroom. One of the factors is the teacher conducts reading activity monotonously. Therefore, the teacher should give a certain technique which appropriates to help the students in comprehending the reading text. The purpose of this study was to know whether or not there was any significant difference of students’ reading abilities after being taught by using Jigsaw Technique. This study used quantitative experimental research design. The subject of this study was the tenth graders of SMAN 1 Patianrowo. The sample of this study was taken by using random sampling. The instrument was writing test (pre-test and post-test) which about a narrative text. The data was gained from the students’ test score. After comparing the students’ test scores of experimental and control groups in the post-test, the result showed that there was significant difference of students’ reading abilities after being taught by Jigsaw technique. It was proven by the means score of experimental group was higher than that of controlled group. The difference of the means score was 88.0556. Moreover, the sig (2-tailed) was 0.02 and it was lower than 0.05. Based on this findings, it is suggested that Jigsaw technique can be used by the teachers to improve student’s ability in reading narrative text. Keywords: Reading, Narrative Text, Jigsaw Technique Abstrak Membaca adalah keterampilan reseptif yang harus dipelajari oleh siswa sebelum mereka belajar keterampilan lainnya. Berdasarkan pra observasi peneliti, mahasiswa sering merasa bahwa membaca adalah kegiatan yang membosankan di kelas. Salah satu faktor adalah guru mengajar membaca dengan cara yang monoton. Oleh karena itu, guru harus memberikan teknik tertentu yang tepat untuk membantu siswa dalam memahami teks bacaan. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada atau tidak perbedaan yang signifikan dari kemampuan membaca siswa setelah diajar dengan menggunakan teknik jigsaw. Penelitian ini menggunakan desain penelitian eksperimental kuantitatif. Subjek penelitian ini adalah siswa kelas X SMAN 1 Patianrowo. Subjek penelitian ini diambil dengan menggunakan random sampling. Instrumen yang digunakan adalah test (pre-test dan post-test) tentang teks narasi. Data penelitian diperoleh dari nilai tes siswa. Setelah membandingkan siswa nilai tes dari kelompok eksperimen dan kontrol dalam post-test, hasilnya menunjukkan bahwa ada perbedaan yang signifikan dari siswa dalam kemampuan membaca setelah diajar dengan teknik Jigsaw. Hal ini dibuktikan dengan nilai post-test dari kelompok eksperimen lebih tinggi daripada kelompok kontrol. Perbedaan nilainya adalah 88,0556. Selain itu, sig (2-tailed) adalah 0,02 dan itu lebih rendah dari 0,05. Berdasarkan hasil tersebut, peneliti menganjurkan bahwa guru sebaiknya menggunakan teknik jigsaw untuk meningkatkan kemampuan siswa dalam membaca teks narasi Kata Kunci: Kemampuan membaca, Teks narasi, Teknik Jigsaw